Changes in Serum Pain Mediators, Stress Response, Inflammatory Markers, and Coagulation Function in Lumbar Disc Herniation Patients Treated by Musculoskeletal Ultrasound-Guided Needle-knife - Wu, Jiaqi; Chen, Ming; Liu, Wenlong; Jiang, Jiaming; Chen, Sihan; Liu, Tingyu; Liu, Xiaoyan (Journal of Medical Biochemistry, 2025)
Objective: To investigate the impacts of musculoskeletal ultrasound (MSK-US)-guided needle-knife on serum pain mediators, stress response, inflammatory markers, and coagulation function in lumbar disc herniation (LDH) patients.Methods: We recruited 100 LDH patients admitted between February 2024 and January 2025 and assigned them to an MSK-US group (52 cases undergoing MSK-US-guided needle-knife) and a conventional group (48 cases receiving conventional needle-knife). Peripheral venous blood was collected before and within 2 hours postoperatively for IL-6, TNF-α, SP, 5-HT, and hs-CRP measurements by ELISA, Cor, E, and NE determination using an automatic biochemical analyzer, β-EP detection by chemiluminescent immunoassay, and APTT, PT, FIB, and D-D quantification with a coagulation analyzer. Dynamic changes in these biomarkers were analyzed by between- and within-group comparisons.Results: Both groups demonstrated postoperative reductions in SP and 5-HT and an elevation in β-EP (P0.05). The MSK-US group showed lower postoperative levels of Cor, E, NE, IL-6, hs-CRP, D-D, and FIB than the conventional group (P
Keywords: musculoskeletal ultrasound; needle-knife; stress response; inflammation; coagulation function